Radical right movement parties in Europe - Caiani, Manuela 1976-; Císař, Ondřej 1974- (Extremism and Democracy, 2018)
Cover -- Endorsement Page -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- List of figures -- List of tables -- Notes on contributors -- List of abbreviations -- Part I Theory -- Chapter 1 Radical Right Movement Parties in Europe: an introduction -- Note -- References -- Chapter 2 Movements, parties, and movement parties of the radical right: towards a unified approach? -- Introduction: background story -- Radical right movement parties -- Party-movement interactions -- Our framework -- Notes -- References -- Part II Western Europe -- Chapter 3 Alternative für Deutschland: from the streets to the Parliament? -- Introduction -- Populism in Germany - difficult cultural opportunities -- Origins of the AfD and context of political and discursive opportunities -- From opportunities to resources: program and voters of the AfD -- The recipe for success: strategy and discourses of the AfD -- Conclusions -- Notes -- References -- Chapter 4 UKIP and the UK's radical right: a tale of movement party success? -- Introduction -- 1993-2010: survival on the political fringe -- 2010-2015: UKIP as a serious electoral challenger -- UKIP during the EU referendum: the shift into movement politics -- The price of success: UKIP fractures after the 'Brexit' vote -- Conclusion -- Notes -- References -- Chapter 5 Still a radical right movement party? Political opportunities, party strategy and the cultural context of the Front National in France -- Introduction -- Conclusion -- Notes -- References -- Chapter 6 Neo-fascist movement parties in Italy: the extreme right between electoral and protest politics -- Introduction -- Data and methods -- Political and cultural opportunities for far-right mobilization: Italy's post-war fascism -- The Italian extreme right: electoral and protest politics -- Conclusion -- Notes -- References.